The study of cationic modification of welan gum - Norhanis, Arbaa′In; Rasidi, Roslan; Jamil, Ismail; Mohd Hasbi, Ab. Rahim; Farizah Khairin, Mohd Tahir (Trans Tech Publications, 2020)
In the present study, welan gum (WG) was modified with a quaternary amine group producing cationic welan gum (CWG) to enhance its thermal and viscosity properties. N-(3-chloro-2-hydroxypropyl) trimethyl ammonium chloride (CHPTAC) was used as the source of the quaternary amine group. The effect of CHPTAC amount in the presence of NaOH was investigated and analyzed using Fourier transform infrared (FTIR), Field emission scanning electron microscope (FESEM), thermal and viscosity analysis. The viscosity results were increases as the amount of CHPTAC increased. From the thermal analyses, it is observed that the CWG has better thermal resistance compared to WG. This study showed that modification of WG by attaching quaternary amine group on the hydroxyl group is promising for the exploration of the high-temperature reservoir.